Anaplastic astroblastoma: a rare glial tumour. (30th September 2011) - Binesh, Fariba; Akhavan, Ali; Navabii, Hossein; Mehrabaniyan, Mohammadreza
Abstract : Astroblastoma is a rarely diagnosed primary brain neoplasm whose histogenesis has been clarified recently. It occurs in children and young adults and presents as a well-circumscribed, contrast enhancing lesion in the cerebral hemisphere. Here the authors present a case of 25-year-old woman with an astroblastoma in the left frontal convexity that was excised. The characteristic radiological and histopathological features of this case are described. An astroblastoma should be included in the differential of a localised brain tumour, especially in a young patient.